Does the Belt and Road Initiative increase the green technology spillover of China’s OFDI? An empirical analysis based on the DID method - Liu, Zhizhong; Liu, Guangyue; Zhang, Ping (Frontiers in Environmental Science, 2022)
The pollution caused by foreign investment has become a serious concern of the host government and academia, many studies have discussed much about the environmental impact of China’s OFDI in countries along the Belt and Road Initiative (BRI) region, but ignored the impact of the BRI itself on China’s OFDI. This paper uses the Global Malmquist-Luenberger index to measure the green technology spillover of China's OFDI from 2005 to 2018, and studies the impact of BRI on this spillover effect with the DID(Difference-in-difference) method. The results show that: (1) the BRI has significantly increased the green technology spillover of China’s OFDI in countries along the routes. The heterogeneity study shows that such an effect is significant in middle-or-low income countries with high institutional quality or poor environmental performance, but not obvious in the other countries. (2) The BRI promotes the green technology spillover through the mechanism of increasing R&D investment, improving the environmental system, and accelerating the flow of production factors. This study provides a useful reference for how to develop a greener OFDI and promote the sustainable development of regional cooperation.